‘Où peut-on être mieux?’ Masonic music and musicians in 19th-century Brussels - Vergauwen, David (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2014)
The researcher David Vergauwen has defended a PhD-thesis, entitled “‘Où peut-on être mieux?’ Masonic music and musicians in 19th-century Brussels” at the Free University of Brussels (VUB) in Belgium the 21st of May 2014.